Exercise tolerance in intermittent cycling: application of the critical power concept - Chidnok, W.; Dimenna, F. J.; Bailey, S. J.; Vanhatalo, A.; Morton, R. H.; Wilkerson, D. P.; Jones, A.M. (Medicine & Science in Sports & Exercise, 2012)
Purpose: This study tested the relevance of the critical power (CP) model for explaining exercise tolerance during intermittent high-intensity exercise with different recovery intensities.